2017
DOI: 10.1101/188946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulator of calcineurin-2 is a centriolar protein with a role in cilia length control

Abstract: Almost every cell in the human body extends a primary cilium. Defective cilia function leads to a set of disorders known as ciliopathies characterised by debilitating developmental defects affecting many tissues. Here we report a new role for regulator of calcineurin 2, RCAN2 in primary cilia function. It localises to centrioles and cilia and is required to maintain normal cilia length. RCAN2 was identified as the most strongly upregulated gene from a comparative RNAseq analysis of cells in which expression of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…4 B). Additionally, investigation into RCAN2, the most highly upregulated gene overall, similarly corroborated the RNA-seq results at the protein level ( Stevenson et al, 2017 preprint ).
Fig.
…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…4 B). Additionally, investigation into RCAN2, the most highly upregulated gene overall, similarly corroborated the RNA-seq results at the protein level ( Stevenson et al, 2017 preprint ).
Fig.
…”
Section: Resultssupporting
confidence: 66%
“…We found that giantin is not responsible for trafficking of GALNT3 to the Golgi, so transcriptional down-regulation of this enzyme at least is not the result of an anterograde trafficking defect. In addition, we do not detect any defects in cilia formation or function in giantin-KO cells ( Stevenson et al, 2017 ) or KO zebrafish ( Bergen et al, 2017 ) despite robust phenotypes following acute knockdown (using RNAi; Asante et al, 2013 ; Bergen et al, 2017 ). Our previous work showed that knockdown of giantin expression using RNAi resulted in defects in cilia formation and function ( Asante et al, 2013 ; Bergen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In particular, we observed PxIxIT-dependent biotinylation of proteins that map to the distal end of centrioles, including interacting partners CCP110 and CEP97: These proteins, which were selectively biotinylated by sub-set of BirA*-tagged centrosomal proteins in other studies (Firat-Karalar et al, 2014;Gupta et al, 2015), bind calmodulin and negatively regulate ciliogenesis (Spektor et al, 2007;Tsang et al, 2006). Previous reports of CN co-purification with Cep97 (Fogeron et al, 2013), and modulation of ciliary length by RCAN2, the CN regulator (Stevenson et al, 2018), further suggest a role for CN at centrosomes/cilia. Our attempts to detect CN enrichment at centrosomes have been unsuccessful (data not shown) and may indicate that CN-centrosome interactions are limited, transient, and/or temporally regulated.…”
Section: Discussionmentioning
confidence: 63%